CORAL FISH POPULATION CHANGES IN THE SURROUNDING ARTIFICIAL REEFS OF THE LEBAH COASTAL WATERS, KARANGASEM, BALI - Amran Ronny Syam; Isa Nagib Edrus; Sri Turni Hartati (Research Center for Fisheries, 2007)
The Directorate General of Fisheries deployed some artificial reefs in 1991 for habitat enhancement in Lebah coastal waters that have already degraded. This study was the 4th time monitoring of fifteen years of restoration period that aimed to identify changes of coral fish population in the vicinity of the artificial reefs.